Upregulation of CCNB2 and Its Perspective Mechanisms in Cerebral Ischemic Stroke and All Subtypes of Lung Cancer: A Comprehensive Study - Li, Ming-Jie; Yan, Shi-Bai; Chen, Gang; Li, Guo-Sheng; Yang, Yue; Wei, Tao; He, De-Shen; Yang, Zhen; Cen, Geng-Yu; Wang, Jun; Liu, Liu-Yu; Liang, Zhi-Jian; et al. (Frontiers in Integrative Neuroscience, 2022)
Cyclin B2 (CCNB2) belongs to type B cell cycle family protein, which locates on chromosome 15q22, and it binds to cyclin-dependent kinases (CDKs) to regulate their activities. In this study, 103 high-throughput datasets related to all subtypes of lung cancer (LC) and cerebral ischemic stroke (CIS) with the data of CCNB2 expression were collected. The analysis of standard mean deviation (SMD) and summary receiver operating characteristic (SROC) reflecting expression status demonstrated significant up-regulation of CCNB2 in LC and CIS (Lung adenocarcinoma: SMD =1.40, 95%CI [0.98–1.83], SROC=0.92, 95%CI [0.89–0.94]. Lung squamous cell carcinoma: SMD=2.56, 95%CI [1.64–3.48]. SROC=0.97, 95%CI [0.95–0.98]. Lung small cell carcinoma: SMD=3.01, 95%CI [2.01–4.01]. SROC=0.98, 95%CI [0.97–0.99]. CIS: SMD =0.29, 95%CI [0.05–0.53], SROC =0.68, 95%CI [0.63–0.71]). Simultaneously, protein-protein interaction (PPI) analysis indicated CCNB2 is hub molecule of crossed high-expressed genes in CIS and LC. Through Multiscale embedded gene co-expression network analysis (MEGENA), a gene module of CIS including 76 genes was obtained and function enrichment analysis of the CCNB2 module genes implied that CCNB2 may participate in the processes in formation of CIS and tissue damage caused by CIS, such as “cell cycle”, “protein kinase activity”, and “glycosphingolipid biosynthesis”. Afterwards, via single-cell RNA-seq analysis, CCNB2 was found up-regulated on GABAergic neurons in brain organoids as well as T cells expressing proliferative molecules in LUAD. Concurrently, expression of CCNB2 distributed similarly to TOP2A as module marker of cell proliferation in cell cluster. These findings can help in the field about the pathogenesis of LC-related CIS and neuron repair after CIS damage.